Stability testing of the Pfizer-BioNTech BNT162b2 COVID-19 vaccine: a translational study in UK vaccination centres. Issue 1 (13th September 2021) - Kudsiova, Laila; Lansley, Alison; Scutt, Greg; Allen, Marcus; Bowler, Lucas; Williams, Sian; Lippett, Samantha; Stafford, Selma; Tarzi, Michael; Cross, Michael; Okorie, Michael
Abstract : Objective: The roll-out of the Pfizer-BioNTech BNT162b2 COVID-19 vaccine has brought many logistical challenges, such as the absence of comprehensive stability data leading to strict handling instructions during dilution and administration. Accidental mishandling therefore presents challenging clinical dilemmas, which often led vaccine providers to err on the side of caution and discard mishandled vials rather than risk administering ineffective vaccine. This study aims to answer key questions about the vaccine's stability to allow for a more informed decision-making process should a non-conformity occur. Methods: Residual vaccine in freshly used, but appropriately stored vials collected from vaccination centres in Brighton, UK, were tested after exposure to various handling conditions and analysed by dynamic light scattering to determine the size of the lipid-mRNA nanoparticles, and gel electrophoresis to visualise the mRNA integrity and separation from the lipid formulation. Results: Knocking or dropping vaccine samples from small heights resulted in lowest levels of instability, indicating low risk of compromising clinical efficacy. However, repeated drawing and injecting through 23 G needles at high speed and, more significantly, shaking and vortexing led to progressive increase in the size and polydispersity index of the lipid-mRNA nanoparticles, coupled with or caused by up to ~50% release of mRNA from the lipid formulation. This is thought to impact the vaccine's efficacy due to lack of free mRNA protection and cellular internalisation. Conclusions: These results reiterate the importance of adhering to the manufacturer's instructions on handling, especially with regard to shaking and exposing the vaccine to excessive vibration.